Measuring Determinants of Satisfaction with Online Courses of Adult Higher Education Among Junior College Students in Chengdu, China - Li, Yanchun (Scholar: Human Sciences, 2025)
Purpose: This study aims to investigate adult higher education junior college students' levels of satisfaction with online course instruction in Chengdu. The method of quantitative survey research is used in this study. Perceived ease of use, perceived usefulness, service quality, information quality, system quality, self-efficacy, and satisfaction were chosen to build the conceptual framework. Research design, data, and methodology: The reliability and validity of constructs are evaluated by item-objective consistency study units of adult education distributed to 498 junior college students at one university. Confirmatory factor analysis and structural equation modeling are employed to assess the data, the accuracy of the matrix, the impact of the key factors, the validity of the hypotheses, and the path coefficients. Data analysis techniques include structural equation modeling (SEM) and confirmatory factor analysis (CFA). Results: Perceived ease of use, perceived usefulness, service quality, information quality, system quality, and self-efficacy significantly impact satisfaction. Conclusions: Consequently, for adult higher education junior college students to acknowledge the effectiveness of online courses, the administrators and teaching staff of continuing education schools in public universities should emphasize the latent variables which have exerted a significant effect on satisfaction with online courses and design relevant teaching reforms according to the results of this quantitative research.